2013 IEEE International Conference of IEEE Region 10 (TENCON 2013) 2013
DOI: 10.1109/tencon.2013.6718817
|View full text |Cite
|
Sign up to set email alerts
|

Multi-target human sensing via UWB bio-radar based on multiple antennas

Abstract: Being capable of sensing human through obstacles, bio-radar is promising in many applications like healthcare, public securities, emergency rescue and so on. In these applications, the presence of human and the human count are among the most important issues that are concerned by people. At present plenty of studies deal with the former issue but there's no study dealing with the latter one. To this end, a framework of determining the count of human targets using ultra-wideband (UWB) bio-radar was presented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The radar was custom-made by the Fourth Military Medical University originally for multi-target human sensing or location [11]. In this paper, it was used for the improved detection of human respiration.…”
Section: The Multistatic Uwb Radarmentioning
confidence: 99%
See 1 more Smart Citation
“…The radar was custom-made by the Fourth Military Medical University originally for multi-target human sensing or location [11]. In this paper, it was used for the improved detection of human respiration.…”
Section: The Multistatic Uwb Radarmentioning
confidence: 99%
“…In recent years, remote sensing of human targets with ultra-wideband (UWB) radar has attracted increasing attention [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Since electromagnetic waves transmitted by UWB radar can penetrate through obstacles, such as clothes, walls, building ruins, etc., this technology can be applied in many areas, like medicine, public security, emergence rescue, and so on [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Promising approaches currently include camera based approaches [27], where is usually easier to perform (in comparison other types of sensors) because of the ability to actually view people. Ultra-wideband radars have also been proposed as a potential solution to the people counting problem [28]. Although the above-mentioned approaches have been proposed, it is still a real challenge to count people in a room accurately.…”
Section: A Passive Infrared Sensors Ultrasonic Sensors and People Cmentioning
confidence: 99%
“…Cross-correlation is a standard method of estimating the degree of correlation between two series. Some studies have reported the application of cross-correlation for human detection [24,25]. In [24], two identical microwave systems are applied to receive echoes simultaneously and the results after a cross-correlation analysis between the signals from the two receivers show that the noises are suppressed, whereas, the energies of the vital signs of life are accumulated because the signals are correlated and the noises are uncorrelated.…”
Section: Introductionmentioning
confidence: 99%
“…The signal-to-noise ratio is improved. In [25], based on the assumption that the respiration of a target detected from different channels are highly correlated, and the correlation between the respiration of different targets and the noises are low among the channels, a correlation analysis is used to restrain the noises and distinguish the human targets. All the above correlation processing has been done between the radar echoes from different channels; however, correlation analysis between signals from a single channel have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%